Hypersensitivity reactions amongst Hungarian Patients with Hereditary Angioedema due to C1-Inhibitor Deficiency - Hanga Réka Horváth, MD; Dávid Szilágyi, MD; Noémi Andrási, MD; Zsuzsanna Balla, MD, PhD; Beáta Visy, MD, PhD; Henriette Farkas, MD, PhD, DSc (World Allergy Organization Journal, 2023)
Background: In hereditary angioedema (HAE) due to C1-inhibitor deficiency (C1-INH-HAE), bradykinin-mediated submucosal and/or subcutaneous angioedema dominates the clinical picture. The deficiency of C1-inhibitor can lead to the over-activation of the complement system. Complement plays an important role in all types of hypersensitivity reactions. On the other hand, during the degranulation of mast cells, heparin is also released amongst other substances. Heparin can activate the plasma kinin-kallikrein system, leading to bradykinin generation. These observations suggest a possible connection between C1-INH-HAE and mast cell-mediated hypersensitivity reactions. Objective: To assess the occurrence of hypersensitivity reactions in the Hungarian C1-INH-HAE population. Methods: Patients filled out a questionnaire of 112 questions, either online or on paper. The questions were about hypersensitivity and C1-INH-HAE symptoms, the relation between these 2, general health, and demographic data. The study protocol was approved by the institutional review board of Semmelweis University, Budapest, and informed consent was obtained from the participants. Results: One hundred and six patients (64 female, 42 male, median age 46 years) responded, with 63.2% having hypersensitivity. Hypersensitivity was provoked by pollen in 25.5% of patients, by contact sensitivity in 22.6%, by food in 21.7%, by insect sting in 19.8%, by pet in 15.1%, by drug in 14.2%, by dust mite in 5.7%, and by mold in 1.9%. In 11 patients, hypersensitivity symptoms appeared after the diagnosis of C1-INH-HAE. Six hypersensitive patients experienced improvement in their symptoms; 42 remained the same, but none experienced worsening after the diagnosis of C1-INH-HAE. In 7.8% of the hypersensitive patients, a C1-INH-HAE attack worsened the hypersensitivity symptoms, while 15.7% of the hypersensitive patients experienced a C1-INH-HAE attack provoked by contact with the provoking factor. Conclusion: While 63.2% of our C1-INH-HAE patients have reported hypersensitivity symptoms, Eurostat's latest data puts the prevalence of self-reported allergies in Hungary at 19.3%. Since in our experience most Hungarian patients report hypersensitivity reactions as allergies, this may support a possible connection between the 2 diseases, but further molecular studies are needed.